Creating a data and technology-enhanced approach to police social service issues: a planning model - Ban, Caroline Conrad (Building trust, effective communication, and transparency between police and community members, 2024)
The landscape of law enforcement is changing. Mental health needs are on the rise, and the vast majority of law enforcement calls for service are already related to social issues. Public safety today requires greater attention to justice, innovation, and new technology. It also requires additional professionals, like social workers, for social service delivery. The future of public safety is clearly a serious situation for police and emergency services organizations and their professional employees. This chapter will (1) discuss the situation that communities and organizations face, (2) identify some of the alternative strategies that can be employed, and (3) provide a process planning model for creating new approaches on the ground in communities. This model emphasizes a data-informed and collaborative approach to the issue.